Low Dose Whole Lung Radiotherapy for Covid-19 Pneumonia: What Is the Current Status? Opinion of The International Geriatric Radiotherapy Group - Nguyen, Nam P.; Vuong, Te; Baumert, Brigitta; Lehrman, David; Gonzalez, Alejandro Chagoya; Vinh-Hung, Vincent; Karlsson, Ulf (Archives of Clinical and Biomedical Research, 2021)
Abstract not available in the source database.